EFFECT OF EXTRACTED LOW DENSITY LIPOPROTEINS SUBSTITUTION ON SOME POST CRYOPRESERVATION SEMEN QUALITY OF HOLSTEIN BULLS - & et al., Al-Ani (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The aim of this study was to investigate the effect of replacement of low density Lipoproteins (LDL) in different concentrations ,exctracted fram egg yolk in the Tris diluents of the Holestion Freizan bulls semen after cooling and different cryopreservation periods . This study was done during the period From September/2014 to March/2015 and a two parts periods . First from September to November /2014 to done the extraction of the low density Lipoprotein which it have be succifully done at the viruses Laportary which belonge to the diagnosis department /state Board of the plant protection /Ministry of Agriclturd (Abu_Gruiab/west of Baghdad).The LDL extraction was done by a procedure with different steps from fresh egg Yolk and the packeges were done after that and preservie it at Refregartor( 5c ,one week only) until used . The second period was began from December/2014 to March/2015 At the Artificial insemination Department /Abu_Gruab which belonge to the General company of the Animal Resources Department services/Ministry of Agricultural (25 Km west of Baghdad ). Four Freigan Bulls at 3_3.5 year old were used to collection the semen (1 eijaculate / bull / week) by artificial vagina . 1 millelitter of semen from each bull was taken and make pooling . Egg yolks was added 20% to the control group it is substituted for the rest of the Low density lipoproteins and different concentrations , amounting to (8% LDL and 10% LDL and 12% LDL). And study the effect of these additions in recipes semen during different periods of Save (cooling 5c) and freeze after(48 hours and one month and two months and three months) .The results of the study reveled that the 8% LDL treatment (T1) group have a significant effect (p≤0.05) on the individual motility ,sperm plasma membrane and acrosome integrity in comparable with the control group at different periods of the preservation.